Study on the ionic conduction properties of alginate-poly (vinyl alcohol) doped ammonium nitrate based bio-polymer blend electrolytes - Nuraziliana, Muhd Ghazali (2023)
The utilization of biomaterial in the production of polymer electrolytes, particularly in electrochemical devices, is currently receiving a great deal of attention. This is because these bio-polymer-based electrolytes have the potential to alleviate the environmental issues, disposal of waste, and human-health concerns through the usage of non-hazardous materials in the energy device system. The aim of this research is to create and characterize a bio-polymer blend electrolyte (BBEs) system made from alginate blended with poly (vinyl alcohol) (PVA) as the bio-polymer host and doped with different contents of ammonium nitrate (NH4NO3) ionic salt. The BBEs system was developed using the solution casting method, and the resulting films showed a transparent, freestanding, and flexible appearance. Fourier transform infrared (FTIR) spectroscopy was used to confirm the complexation occurs in the BBEs. X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM) were used to reveal the amorphous nature and morphology of the BBEs. The results of the thermogravimetric analysis (TGA) showed that the thermal stability of the BBEs has been enhanced as a result of the addition of NH4NO3. Electrical impedance spectroscopy (EIS) was used to measure the ionic conductivity of the BBEs system, where the highest ionic conductivity was revealed to be 5.20 × 10-4 S cm-1 when 35 wt.% of NH4NO3 was added into the system. The increase of ionic conductivity at room temperature was due to the enhanced amorphous nature as well as complexation between the lone pair oxygen at the Alg-PVA bio-polymer chain backbone and H+ from NH4NO3. The effect of temperature on the ionic conductivity of BBEs revealed that all BBEs obeyed Arrhenius behavior and displayed a lower activation energy, Ea of 0.10 eV for the highest conducting BBEs. Based on the dielectric response analysis, it was revealed that the ionic mobility, μ, number density of charge carriers, η, and diffusion coefficient, D of the H+ were all factors that influenced the ionic conductivity of the BBEs. Through the use of transference number measurement (TNM) analysis, the BBEs with the greatest ionic conductivity was analyzed to determine the ion dominancy. The tion was found to be 0.51, and this finding verified the predominance of H+ in the present BBEs system. Based on these results, this BBEs system has a high potential to be utilized in electrochemical device applications as an electrolyte, specifically in electrical double layer capacitors and proton batteries.